Study on Phosphate Solubilization of Salt Tolerant Soil Yeast Isolates and Effects on Maize Germination and Growth - May Thet New; San San Yu; Zaw Ko Latt (Institute of Advanced Engineering and Science, 2013)
Among 12 isolated soil yeasts, four isolates were selected according to their salt tolerance and these four isolates tolerated 14% NaCl. Moreover, they can tolerant to KCl, MgCl2 and CaCl2. Phosphate solubilization of selected soil yeast isolates were detected in Pikovskaya’s broth supplemented with various NaCl concentrations (ranging from 0% to 10%). They can solubilize insoluble phosphate at all NaCl concentrations. But with increasing NaCl concentration, phosphate solubilization was decreased and the best solubilization was occurred at 6 days incubation period. Above 10% NaCl concentration, these isolates cannot solubilize insoluble phosphate, Ca3(PO4)2. On maize germination under NaCl stressed conditions, it was found that soil yeast isolates enhanced maize germination when compared with uninoculated treatment. Above 0.5% NaCl concentration, germination percentage of maize was obviously different between inoculated and uninoculated treatments. Like in phosphate solubilization, germination percentage was decreased with increasing NaCl concentration. At 2% NaCl concentration, germination was not found. So these isolates tolerated to some degree of NaCl, there is limited range for their functioning. After treating salt affected soils with soil yeast isolates for four weeks, salinity of treated soils was slightly decreased but total nitrogen content, K+, and available nutrients (P and K2O) were slightly increased when compared with those of untreated soil.